Pendampingan Pemanfaatan Microsoft Excel Sebagai Inovasi Digital dalam Optimalisasi Pengelolaan Usaha Milik Mahasiswa - Anni Safitri; Mar’atus Sholikah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
The purpose of this community service is to provide an understanding of the use of Microsoft Excel as a digital innovation in optimizing the management of student-owned businesses. The methods used in this community service are Microsoft Excel training, Q&A sessions, discussions and evaluations. Based on the results of the Q&A assessment and direct application usage practice activities, it is known that out of 30 student participants, 15 students (50%) understand basic accounting concepts and can record in Microsoft Excel, 6 people (20%) already understand basic accounting concepts but have not been able to record in Microsoft Excel, and 9 people (30%) still do not understand the concept of basic accounting recording. The results of the training also showed that most students had not previously optimized technology in business management, and still used manual recording or were not documented at all.